2019
DOI: 10.1073/pnas.1822024116
|View full text |Cite
|
Sign up to set email alerts
|

Renal control of disease tolerance to malaria

Abstract: Malaria, the disease caused byPlasmodiumspp. infection, remains a major global cause of morbidity and mortality. Host protection from malaria relies on immune-driven resistance mechanisms that killPlasmodium. However, these mechanisms are not sufficient per se to avoid the development of severe forms of disease. This is accomplished instead via the establishment of disease tolerance to malaria, a defense strategy that does not targetPlasmodiumdirectly. Here we demonstrate that the establishment of disease tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 41 publications
11
84
1
Order By: Relevance
“…Recent studies confirmed the central role of heme in the pathophysiology of malaria [81,82]. Moreover, extracellular heme accumulation is not limited to malaria;…”
Section: Discussionmentioning
confidence: 79%
“…Recent studies confirmed the central role of heme in the pathophysiology of malaria [81,82]. Moreover, extracellular heme accumulation is not limited to malaria;…”
Section: Discussionmentioning
confidence: 79%
“…Proximal tubules within the organoids were able to carry out endocytosis, as evidence of functional maturity [99]. Kidney organoids can be used as a platform to develop new drugs to treat chronic kidney disease [113].…”
Section: Kidney Idosmentioning
confidence: 99%
“…As a prototypical example accumulation of labile heme in plasma and urine during Plasmodium infection has been shown to induce pronounced disease tolerance to malaria. Specifically, the heme-induced tolerance response prevents the development of acute kidney injury, a clinical hallmark of severe malaria [34]. How do parenchymal organs cope with resistance and tolerance responses of the immune system?…”
Section: Outlook: Resistance and Tolerance Responses Beyond The Immunmentioning
confidence: 99%